Озерненість та інші ознаки продуктивності рослин F₁ пшениці м’якої від схрещення форм з транслокаціями 1BL/1RS і 1AL/1RS - Созінов, І.О.; Козуб, Н.О.; Бідник, Г.Я.; Дем’янова, Н.О.; Блюм, Я.Б.; Созінов, О.О. (Фактори експериментальної еволюції організмів, 2016)
Aim. Seed set and other productivity traits were studied for looking into the possibility of using hybrids between forms with two wheat-rye translocations in heterotic breeding. Methods. A number of productivity traits of a plant and a spike were analyzed in F₁ plants from four crosses between forms with 1AL/1RS and 1ВL/1RS. Results. F₁ hybrids with the simultaneous presence of 1AL/1RS and 1ВL/1RS translocations had reduced seed set in comparison with the parental forms. The magnitude of reduction in seed set depended on the genotype. F₁ plants from the cross 7086 AR × Myronivska 67 showed heterosis for grain yield number of productive tillers and spikelets per spike. Conclusions. The simultaneous presence of two translocations 1AL/1RS and 1ВL/1RS in F₁ plants results in the reduction of seed set, whose magnitude depends on the genotype. However highly heterotic hybrids may be produced with certain crosses.